Wittgenstein and justice - "Pitkin, Hanna Fenichel" (London, 1993)
Hanna Pitkin argues that Wittgenstein's later philosophy offers a revolutionary new conception of language, and hence a new and deeper understanding of ourselves and the world of human institutions and action.
Keywords: "Philosophy, Western"